Highly Stable Photonic Local Carriers for Phased Array Receiver System - Khan, M. R. H.; Hoque, M. A. (Engineering, Technology & Applied Science Research, 2020)
In this paper, a complete system analysis of photonic local carrier generation technique has been investigated. The generated carrier is potentially suitable to replace the existing microwave/RF Local Carrier (LC) used in commercial Low Noise Blocks (LNBs) for the Phased Array (PA) receiver system. The optical LC generated from heterodyning of two commercialized lasers is being stabilized with an Optical Frequency Lock Loop (OFLL). This approach resulted in a generated carrier at the Ku-band (10.7GHz to 12.75GHz) signal received from a PA receiver. Various loop parameters of the OFLL have been investigated to comply with the requirements of the commercial LNBs The proposed OFLL shows a 2400 fold improvement in the frequency stability at 1000s averaging time compared to its free running condition. It is also demonstrated that with an optimized loop gain of 30dB, the loop response time of the proposed OFLL becomes 11μs.